2002
DOI: 10.1074/jbc.m202653200
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα Regulates Hepatic Transcription of Hepcidin, an Antimicrobial Peptide and Regulator of Iron Metabolism

Abstract: Originally identified as a gene up-regulated by iron overload in mouse liver, the HEPC gene encodes hepcidin, the first mammalian liver-specific antimicrobial peptide and potential key regulator of iron metabolism. Here we demonstrate that during rat liver development, amounts of HEPC transcripts were very low in fetal liver, strongly and transiently increased shortly after birth, and reappeared in adult liver. To gain insight into mechanisms that regulate hepatic expression of hepcidin, 5-flanking regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
177
2
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(196 citation statements)
references
References 39 publications
13
177
2
4
Order By: Relevance
“…CCAAT/enhancer binding protein (C/EBP) was demonstrated to bind this upstream region (Fig. 3B), and C/EBP could activate hepcidin expression in hepatocytes (Courselaud et al, 2002). This finding is supported by a recent study, which demonstrated that the transcription of hepcidin was suppressed by E2 treatment in hepatocytes, HuH7 and HepG2 cells, and this down-regulation could be blocked by the treatment of the E2 antagonist ICI 182780 (Yang et al, 2012).…”
Section: Elevated Hepcidin Expression In Liver Devoid Of Endogenous Esupporting
confidence: 71%
“…CCAAT/enhancer binding protein (C/EBP) was demonstrated to bind this upstream region (Fig. 3B), and C/EBP could activate hepcidin expression in hepatocytes (Courselaud et al, 2002). This finding is supported by a recent study, which demonstrated that the transcription of hepcidin was suppressed by E2 treatment in hepatocytes, HuH7 and HepG2 cells, and this down-regulation could be blocked by the treatment of the E2 antagonist ICI 182780 (Yang et al, 2012).…”
Section: Elevated Hepcidin Expression In Liver Devoid Of Endogenous Esupporting
confidence: 71%
“…Hepcidin deficiency has been associated with the loss of hepcidin itself, HJV, HFE, or TfR2 in humans 3,[7][8][9] and with the inactivation of CCAAT/enhancer binding protein ␣ and mothers against decapentaplegic homolog 4 (Smad4) in mice. 10,11 As for the contribution of nongenetic factors, ethanol abuse (long associated with iron overload) is now believed to inhibit hepcidin transcription. 12,13 Similar effects can be produced by toxic and viral insults (for example, the hepatitis C virus may inhibit hepcidin expression 14 ).…”
Section: Disruption Of Homeostasis: Insulin and Diabetes Hepcidin Anmentioning
confidence: 99%
“…Hepcidin expression is probably transcriptionally regulated (3,4), although the exact mechanisms are not completely defined. The circulating peptide acts as the master regulator of cellular iron export by controlling the concentration of ferroportin (Fpn), an iron exporter present on the basolateral surface of intestinal enterocytes and placental cells and on macrophages and hepatocytes (5)(6)(7).…”
mentioning
confidence: 99%